FEATURES OF CARDIORESPIRATORY ADAPTATION OF THE LATE PREMATURELY NEWBORNS IN THE EARLY NEONATAL PERIOD - Soloviova, H.O.; Pokhylko, V.I.; Tsvirenko, S.M.; Hasiuk, N.I.; Klymchuk, Y.Y. (World of Medicine and Biology, 2018)
The process of the adaptation of premature infants is complex and requires careful monitoring of all vital parameters in the post-natal period.Purpose: to study the characteristics of the respiratory pattern and the heart rate of the "late preterm" children in the early neonatal period.Method. There are 42 preterm infants with gestational age from 35 to 36 weeks were examined in the first day of life. There were 25 (59%) boys and - 17 (41%) girls. The children were divided into two groups: I group - newborns were transferred from the maternity ward to the department of the newborns with mothers (n = 22), and the II group - newborns (n = 20) which in the first day of their life were separate from the mothers. Mothers of premature newborns of group I used the method of "kangaroo", the average duration of which during the day was 7.6 ± 0.8 hours, newborns II groups during the day had contact with their mother only during feeding, the average duration of which during the day was 2, 1 ± 0.5 hours. All patients underwent somatic and neurological examination, 24- hours ECG with rheopneumograms monitoring in the early neonatal period. Results. Analysis of the pregnancy and childbirth showed that all mothers had some deviations from the norm. Among the complications of obstetric and gynecological history, the most commonly encountered the threat of abortion at different times - in 49.0% of women in group I and 50.0% in group II, placental dysfunction - 63.3% and 60.0%, anemia in the second half of pregnancy - by 72.0% of women in each group. All "late premature birth" children had a periodic type of respiration with respiratory pauses from 3 to 11 seconds in children of the I group and from 4 to 16 seconds in infants of the II group.Conclusion. Periodic breathing and respiratory pauses during the first day after birth are characteristic respiratory patterns of late premature infants. The number of respiratory pauses during the day was probably (p
Keywords: "late premature" infants; postnatal adaptation; kangaroo method; rheopneumography; daily ECG monitoring